Physico-Chemical Study of Tetrabutylammonium Bromide Solutions in Methanol and Ethanol at Different Temperatures - Abbas, Hawazin A; Al-Dujaili, Amar H; Abdul-Ghani, Mohammad J (Al-Nahrain Journal of Science, 2012)
Viscosity and density measurements at concentration range (0.0040-0.1661mole/L) for the tetrabutylammonium bromide (TBABr) solutions in methanol and ethanol at various temperatures (298.15, 303.15 and 308.15 K) are reported. The viscosity A and B coefficient was calculated from the Jones–Dole equation and found to be decreased from methanol to ethanol. The Gibbs free energy of viscons flow of (TBABr) solutions in methanol and ethanol we’re calculated from experimental viscosity measurements using Eyring equation. The apparent molal volumes   for these solutions at different temperatures we’re also obtained from experimental density measurements.